The efficacy and risks of preoperative embolization of spinal tumors. (14th August 2015) - Awad, Al-Wala; Almefty, Kaith K; Ducruet, Andrew F; Turner, Jay D; Theodore, Nicholas; McDougall, Cameron G; Albuquerque, Felipe C
Abstract : Background: The goal of preoperative embolization of spinal tumors is to improve surgical outcomes by diminishing the vascular supply to the tumor to reduce intraoperative blood loss and operative time. Objective: To report our institutional experience with spinal tumor embolization and review the present literature. Methods: Clinical records from January 1, 2001 to December 31, 2012 were reviewed and analyzed. Angiograms were used to calculate the percentage reduction in tumor vascularity, and relevant clinical and operative data were collected and analyzed. Results: Thirty-seven patients underwent preoperative spinal tumor embolization (24 metastatic and 13 primary lesions) and were included in the study. One complication resulted in transient lower extremity weakness and was attributed to post-embolization swelling, which fully resolved after surgical resection. The transient neurological complication rate was 1/37 (3%) and the permanent rate was 0/37 (0%). The average surgical estimated blood loss (EBL) was 1946 mL (100–7000 mL) and the average operative time was 330 min (range 164–841 min). After embolization, tumor blush was reduced by 83% on average. Average pre- and postoperative modified Rankin Scale scores were 2.10 and 1.36, respectively (p=0.03). Cases in which tumor blush was decreased by ≥90% (classes 1 or 2) after embolization had significantly less operative blood loss than those cases in which <90% (classes 3 or 4) was achieved (mean EBL 1391 vs 2296 mL, respectively, p=0.05). Conclusions: Spinal tumor embolization is a safe procedure, is associated with few complications, and may improve surgical outcomes by limiting intraoperative blood loss and reducing operative time.